Studyon Characteristics and Shelf Life Prediction of Cashew Appels Using Modified Atmosphere Packaging System - La Rianda; . Sutrisno; Rizal Syarief; I Wayan Budiastra (Jurnal Keteknikan Pertanian, 2000)
The aims of this research are: I) to identzJL the changes ofphysiologic characteristics of cashew apples during storage under MAP system; 2) to verzfv the changes of their quality during storage; and 3) to establish the optimum gaseous compotition range in the MAS system. To completed the research, the experimen was conducted by four steps activities as follows: I) the measurement of respiration rate; 2) establishment of the range of modijied atmosphere storage for cashew uppels; 3) cojitputingthe packaging area and selecting the kind of plastic film; 4) prediction of shelf lge for cashew appels during srorage under MAP system.